PENGARUH MOTIVASI, KEPUASAN KERJA, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN THE PARK LANE HOTEL JAKARTA - Sri Ayu Rahayu; Meylani Tuti (Human Capital Development, 2019)
Purpose- This study aimed to analyze the effect of motivation, work satisfaction, and leadership on employee performance at The Park Lane Hotel Jakarta in 2018. Design/methology/approach- The data were obtained from the presentation of data from the respondents (questionniare), and the result of other studies that relevan with the object studies, in this case the primary data from The Park Lane Hotel Jakarta. The method used is descriptive quantitative analyze, sample in this studies amounted 120 employee with a sampling technique that by using accidental sampling. The statistical used in this study is multiple regression analyze using SPSS 20. Findings- The finding of this study suggest that the motivation variable, work satisfaction and leadership simultaneously (together) and significally effect on employee performance in The Park Lane Hotel Jakarta in 2018. This is evidence by the result of the F test with a significance level below 0,05 and the result is 0 the meaning is the motivation, work satisfaction, and leadership variable are partially and significantly effect on employee performance. This is evidenced by the result of t test, independent variable are affect each dependent variable if the significance level below 0.05. motivation with significance level of 0,031 and work satisfaction with significance level of 0,016 and leadership with significance level of 0,019. The most variable affecting employee performance is motivation.